Synthesis of silver nanoparticles by Bacillus subtilis T-1 growing on agro-industrial wastes and producing biosurfactant - Płaza, Grażyna Anna; Chojniak, Joanna; Mendrek, Barbara; Trzebicka, Barbara; Kvitek, Libor; Panacek, Ales; Prucek, Robert; Zboril, Radek; Paraszkiewicz, Katarzyna; Bernat, Przemysław (IET nanobiotechnology, 2016)
In this study, culture supernatnats of Bacillus subtilis T-1 growing on brewery effluents and molasses was used for silver nanoparticles (Ag-NPs) synthesis. The biosurfactant production of B. subtilis T-1 was confirmed by the detection of genes in the genome and by the identification of the product in the supernatants. The genes for synthesis of surfactin (sfp, srfAA) and iturin (ituC) were noted by PCR reactions. Also, in examined culture supernatants the presence of C13, C14 and C15 surfactin homologues with the sodiated molecules [M + Na](+) at m/z 1030, 1044 and 1058 was confirmed using LC/MS/MS analysis. The formation of NPs in the culture supernatants was confirmed by UV-vis spectroscopy. The dynamic light scattering measurements and transmission electron microscopy images showed the nanometric sizes of the biosynthesised Ag-NPs which ranged from several nm to several tens of nm depending on the used culture supernatant. Biological properties of Ag-NPs were evaluated by binding of Ag-NPs with DNA isolated from the Escherichia coli ATCC 25922 and B. subtilis ATCC 6633. Biogenic Ag-NPs were actively bound to DNA in increased concentration which could be the one important mode of antibacterial action of the Ag-NPs.
Keywords: povrchově aktivní látky; Tandem Mass Spectrometry; Bacillus subtilis; Surface-Active Agents; Molasses; melasa; Agriculture; lipopeptidy; kovové nanočástice; Silver; velikost částic; Lipopeptides; tandemová hmotnostní spektrometrie; cyklické peptidy; průmyslový odpad; Peptides, Cyclic; zemědělství; stříbro; Industrial Waste; transmisní elektronová mikroskopie; Microscopy, Electron, Transmission; Particle Size; Metal Nanoparticles